Towards large-scale decision support for farmers: site and season specific advice for maize agronomy in Malawi - Chikowo, Regis; Christensen, Kennet; Snapp, Sieglinde S. (2020)
In much of sub-Saharan Africa, national agricultural extension systems are severely constrained as extension worker: farmer ratio can be as high as 5000. A network of lead farmers complements the efforts of extension personnel. Regrettably, this combined effort falls far too short for effective dissemination of technologies to farmers. Interactive voice response (IVR) is a potential technology to reach farmers with agronomic messages, especially those that own cellphones in remote areas. These farmers could become hotspots for sustained change.